Prolapsed Intervertebral Disc among Symptomatic Motorcycle Riders in a Tertiary Care Setting in Karachi, Pakistan - Silvia, Sana; Ali, Farhad; Hussain, Syed Muhammad; Bhatti, Talha; Khan, Atiq Ahmed; Shaukat, Shuja (Biological and Clinical Sciences Research Journal, 2025)
Motorcycle commuting dominates transport in South‑Asian megacities; prolonged vibration and flexed posture plausibly accelerate lumbar disc degeneration. Objective: To determine the frequency of MRI‑confirmed prolapsed intervertebral disc (PID) and its clinical correlates among motorcycle riders. attending the neurosurgery outpatient department of Dr Ruth Pfau Civil Hospital, Karachi, from 1st September 2024 to 28th February. Methods: This cross-sectional study was conducted at the neurosurgery outpatient department of Dr Ruth Pfau Civil Hospital, Karachi, over a period of six months, from 1st September 2024 to 28th February 2025. Adult motorcycle riders (18–50 years) presenting with low‑back pain (LBP) and a recent lumbar MRI were recruited by convenience sampling. A 26-item questionnaire captured socio-demographics, occupational profile, riding metrics, pain characteristics, and radiological level of PID. Descriptive statistics, χ² tests, and Pearson correlations were computed in SPSS v26. Results: Of 198 riders (94.9 % male, mean age 36.1 ± 9.9 years), 56 (28.3 %) had MRI‑verified PID. Riders on uneven roads exhibited a similar frequency to those on relatively even roads (25.8 % vs 32.1 %; χ² = 0.62, p = 0.431). Pain radiated to the legs in 78 participants (χ² = 7.2, p = 0.028). Daily riding hours averaged 3.3 ± 1.6 and showed a weak positive correlation with early pain onset (r = 0.18, p = 0.012). Conclusion: In this cross-sectional study of symptomatic motorcycle riders attending a tertiary neurosurgical clinic, approximately one in four exhibited MRI-confirmed prolapsed intervertebral disc. Pain radiation strongly correlated with symptom severity, while self-reported road unevenness did not significantly predict disc pathology. These findings suggest that while mechanical exposure from riding may contribute to disc degeneration, the risk is influenced by multiple interacting factors. The integration of ergonomic education into primary care and licensing systems, along with improved road infrastructure, may help mitigate the spinal health burden among urban motorcyclists.